Sporadic Epstein syndrome with macrothrombocytopenia, sensorineural hearing loss and renal failure. Issue 5 (21st September 2015) - Makino, Shigeru; Kunishima, Shinji; Ikumi, Aki; Awaguni, Hitoshi; Shinozuka, Jun; Tanaka, Shin‐ichiro; Maruyama, Rikken; Imashuku, Shinsaku
Abstract: We report here a sporadic case of Epstein syndrome, one of the MYH9 disorders. A Japanese boy was first noted to have thrombocytopenia at 3 years of age. Blood smear showed giant platelets but no Döhle‐like bodies in the neutrophils. He had no family history of thrombocytopenia, hearing loss, and/or renal failure. Thrombocytopenia took a chronic course and platelet count fluctuated in the range 18 000–46 000/μL, not responding to i.v. immunoglobulin or prednisolone treatment. The patient had episodes of gross nasal bleeding at 7 and 18 years of age. Mild hearing loss was suspected at 6, and proteinuria was first noted at 14 years of age. At the development of renal failure at 24 years of age, he was identified to have de novo R702H MYH9 mutation. This case illustrates the importance of suspecting MYH9 disorder even in cases of chronic macrothrombocytopenia without family history.